Suicides and their preventive interventions possibilities: are there some relationships between mechanisms and different mental disorders? - Matlach, Radek; Makovická, Mária; Miklošová, Mária; Makovický, Pavol; Muri, Jozef; Rimárová, Kvetoslava; Samasca, Gabriel; Michalčová, Patricie; Makovický, Peter (Bratislavské lekárske listy, 2023)
Suicides are one of the topics discussed around the world. This problem receives large space in scientific and professional literature, in order to eliminate its occurrence. Mechanisms of suicides are determined by whole spectrum of reasons determined by/depending on physical and psychological health. The objective of this work is to document the differences in mechanisms and realization of suicides by mentally sick people. Ten cases of suicides are reported in the article: three of which in people with a history of depression of the victim noted by family members, one with treated depression, three with anxiety-depressive disorder and three schizophrenic patients cases. There are five men and five women. Four of these women overdosed themselves by medicaments and one jumped out of a window. Two men shot themselves, two hanged themselves and one jumped out of a window. Persons without anamnestically proven psychiatric diseases end their lives mostly because of inconclusive situation or as a result of balancing their whole life (usually with good plan and preparation of the act). Persons with treatment of depression or anxiety-depressive disorder kill themselves mostly after several “unsuccessful” attempts. In case of victims with schizophrenia suicides follow a hardly predictable sequence of actions which sometimes do not seem to have any logic. Differences have been found between victims with and without mental disorders in ways of realization of suicides. Psychological predispositions in mood changes, long-term sadness and threatening suicide should be recognized by family members. Prevention of suicides in cases of people with a history of mental disorders is based on medical treatment and cooperation between the client and family members and a psychiatrist (Ref. 30).